Performance evaluations in Brazilian accounting education: A comparative analysis between IES in front of the CFC Sufficiency Exam - Marçal, Ronan Reis (2019)
The CFC Examination of Sufficiency is mentioned by several authors as a tool for evaluating students' performance in Accounting. Since 2011, the exam was leveraged as a necessary condition to obtain professional accounting registration through Law 12.249 (2010). Although the examination has been applied continuously since the referred Law, its results had not been disclosed, until then, separately by each University. However, in 2017, CFC released the results of the exam applied in the first semester analytically, considering the results obtained by each University. Due to the relevance of the exam and the informational novelty, this study sought to verify if there is a difference in the level of performance obtained by the Accounting students of Brazilian Universities in the CFC Examination of Sufficiency, considering the different characteristics of these Universities as possible determinants of performance. Quantitative methods were used to verify the hypotheses formulated considering a 95% confidence level all the time. The results suggest statistically significant differences of the means of approval in the Examination of Sufficiency for all the observed conditions. The findings of this study contribute to the sphere of research on accounting education in Brazil allowing sectoral analyzes in this area.